2017
DOI: 10.1038/s41598-017-06387-6
|View full text |Cite
|
Sign up to set email alerts
|

Duplication events downstream of IRX1 cause North Carolina macular dystrophy at the MCDR3 locus

Abstract: Autosomal dominant North Carolina macular dystrophy (NCMD) is believed to represent a failure of macular development. The disorder has been linked to two loci, MCDR1 (chromosome 6q16) and MCDR3 (chromosome 5p15-p13). Recently, non-coding variants upstream of PRDM13 (MCDR1) and a duplication including IRX1 (MCDR3) have been identified. However, the underlying disease-causing mechanism remains uncertain. Through a combination of sequencing studies on eighteen NCMD families, we report two novel overlapping duplic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…Given the phenotypic similarity observed in Family 3 to both NCMD and PBCRA, it was hypothesised that the disease‐associated genetic variant may be located within the associated loci. Using the WGS SNV and structural variant (SV) call data and manual interrogation of the paired‐end reads using the Integrative Genomics Viewer (IGV; Thorvaldsdóttir, Robinson, & Mesirov, ),) all known NCMD‐associated variants were excluded at both the chr5 and chr6 loci (Bowne et al, ; Cipriani, Silva et al, ; Manes et al, ; Small et al, ). At the PBCRA/MCDR1 locus, 75 SNV variants with MAF < 0.01 (and allele count <3 from NIHR data set), were shared, of which 18 were absent from gnomAD (Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the phenotypic similarity observed in Family 3 to both NCMD and PBCRA, it was hypothesised that the disease‐associated genetic variant may be located within the associated loci. Using the WGS SNV and structural variant (SV) call data and manual interrogation of the paired‐end reads using the Integrative Genomics Viewer (IGV; Thorvaldsdóttir, Robinson, & Mesirov, ),) all known NCMD‐associated variants were excluded at both the chr5 and chr6 loci (Bowne et al, ; Cipriani, Silva et al, ; Manes et al, ; Small et al, ). At the PBCRA/MCDR1 locus, 75 SNV variants with MAF < 0.01 (and allele count <3 from NIHR data set), were shared, of which 18 were absent from gnomAD (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Given the rarity of the phenotype and the discovery of the same variant in two not knowingly related families, we sought to determine whether a common ancestral haplotype could account for the disease. Haplotype sharing analysis (Cipriani, Kalhoro et al, ; Cipriani, Silva et al, ) of SNP‐array data showed that the families had a different chromosomal background at the 6q linkage region (Figure S1). Furthermore, WGS enables the characterisation of every SNV (common or rare) in the linkage region in both families.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations